The results of case study of the implementation of marketing communication tools in the enviromental protection - Kerlesová, Vladislava (Univerzita Pardubice, 2010)
Marketing is an important tool for informing the general public. Its mission is to provide education in the questions of environment protection necessity and sustainable development. The objective of this contribution is to present the results of the case study of practical marketing application in the environment protection field. There is used a quantitative analysis of the regional press for finding out the data.
Keywords: ecology; communication; marketing; environment